1995
DOI: 10.2134/agronj1995.00021962008700040003x
|View full text |Cite
|
Sign up to set email alerts
|

Wind and Windblown Sand Damage to Pearl Millet

Abstract: Pearl millet [Pennisetum gluucum (L.) R. Br.] is grown worldwide in areas affected by wind erosion, but no data on associated damage to millet are available. Laboratory wind tunnel experiments were conducted to determine the kind and extent of damage to millet caused by wind, sandblasting, and burial. In Exp. 1, millet was exposed for 15 min to wind (8, 11, or 14 m s-') or wind + sand (8.3, 25.0, or 41.7 g ,-I-I sand abrader flux) at 8 and/or 16 d after emergence (DAE). Viable leaf area, leaf net photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
(41 reference statements)
3
24
0
Order By: Relevance
“…The greater importance of seedling burial is also supported by its higher score (Table III). The present results are consistent with the ®ndings of Sterk and Haigis (1998) and with past experimental results which have shown that millet, which is the crop most likely to be affected by wind erosion, is rather resistant to sandblasting but is sensitive to burial at the seedling stage as a result of it being sown in small planting holes (Michels et al, 1995a).…”
Section: Consequences Of Wind Erosionsupporting
confidence: 93%
“…The greater importance of seedling burial is also supported by its higher score (Table III). The present results are consistent with the ®ndings of Sterk and Haigis (1998) and with past experimental results which have shown that millet, which is the crop most likely to be affected by wind erosion, is rather resistant to sandblasting but is sensitive to burial at the seedling stage as a result of it being sown in small planting holes (Michels et al, 1995a).…”
Section: Consequences Of Wind Erosionsupporting
confidence: 93%
“…As arthropod damage expressed in plant fossils can be difficult to differentiate from abiotic trauma, we used the criteria outlined by Labandeira (2006, and the references therein) to identify arthropod-generated damage and also to distinguish herbivory from saprotrophy. Most importantly, herbivory damage is typically expressed by stereotypical feeding patterns consistent with modern analogues, the development of reaction tissue around the wound, development of necrotic flaps or veinal stringers around damaged tissue, and distinctive and consistent phytotissue-herbivore linkages that are incompatible with other forms of biological or physical trauma, such as that caused by fungi (Parbery, 1996;Taylor and Osborn, 1996) or abiotic processes (Wilson, 1984;Michels et al, 1995;Wright and Vincent, 1996;Racskó et al, 2010). We sought to assign examples of plant damage to the principal functional feeding groups outlined by Labandeira et al (2007a): viz., external foliage feeding (here subdivided into the categories of leaf-margin feeding, apical feeding, surface feeding and hole feeding), piercing-and-sucking, boring, leaf mining, galling, seed feeding, palynophagy, nectarivory and oviposition.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] Dust storms carry tonnes of top soil from agricultural land and affects the soil resource base and crop productivity on a long-term basis by damaging plant tissue, causing delay in plant development [8][9][10] and accelerates land degradation. [11,12] Moreover, the deposition of dust on irrigation canals and rivers affects the water quality of streams, lakes and oceans. [13][14][15][16][17] A study by Lim et al [18] highlighted the contribution of dust events to the distribution of microbes in the environment from two dust storms in Australia.…”
Section: Introductionmentioning
confidence: 99%